2020
DOI: 10.3390/ma13184174
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Erbium-Doped Yttrium Aluminum Garnet Laser (Er: YAG) Irradiation on Sandblasted and Acid-Etched (SLA) Titanium, an In Vitro Study

Abstract: The treatment of peri-implantitis implies the decontamination of the surface of the fixture. This study aims to analyze the effect of the erbium-doped yttrium aluminum garnet laser (Er: YAG) on sandblasted and acid-etched (SLA) titanium. 30 titanium SLA disks were divided into three groups. In Group 1, the disks were left intact; on the contrary, both Groups 2 and 3 were irradiated with the Er: YAG laser at different settings, with a pulse duration of 300 μs and a period of 30 s. Group 2 was irradiated at 1 W … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…While C and N decreased after debridement, an increase was observed in Ti and O. EDX analysis around dirty implants showed that the lower percentages of C and higher Ti when the surface was cleaned [ 37 , 44 ]. In the studies of Scarano et al, increased surface oxide levels, decreased in porosity, and nano-roughness represented a positive change that could protect titanium against bacterial adhesion [ 43 , 45 ]. The study of Takagi et al reported that C and Ca percentages on dirty surfaces decreased, while Ti percentages increased significantly after debridement with ErL and ErCrL on artificially created calcified areas.…”
Section: Discussionmentioning
confidence: 99%
“…While C and N decreased after debridement, an increase was observed in Ti and O. EDX analysis around dirty implants showed that the lower percentages of C and higher Ti when the surface was cleaned [ 37 , 44 ]. In the studies of Scarano et al, increased surface oxide levels, decreased in porosity, and nano-roughness represented a positive change that could protect titanium against bacterial adhesion [ 43 , 45 ]. The study of Takagi et al reported that C and Ca percentages on dirty surfaces decreased, while Ti percentages increased significantly after debridement with ErL and ErCrL on artificially created calcified areas.…”
Section: Discussionmentioning
confidence: 99%
“…Its use leads to an operating field cleaner from blood and atraumatic work. Additionally, it significantly reduces pain and postoperative edema [ 221 , 222 , 223 , 224 , 225 ]. The use of lasers offers better aesthetic effects compared to other techniques since it does not leave an obvious scar, giving the part of the body where the intervention is performed an excellent restitutio ad integrum [ 221 , 222 , 223 , 224 ].…”
Section: Biostimulation and Laser–graft Interactionsmentioning
confidence: 99%
“…However, the use of the laser gives excellent results on the surfaces of implants that have been attacked by peri-implantitis and have part of the fixture exposed in the oral cavity. The use of the laser decreases the microroughness and porosity of the implants, thus giving a more glossy surface, which prevents the adhesion of bacteria on smooth surfaces [ 225 ]. In their study, Pereira et al reported that the use of the LLLT did not lead to any change in bone regeneration compared to the control group, but there was a noticeable difference in the interface between the implant and the bone, thus allowing for better osseointegration [ 239 ].…”
Section: Biostimulation and Laser–graft Interactionsmentioning
confidence: 99%
“…The Erbium laser was introduced to vaporize and remove tissues and is a versatile laser system used in dermatology [2]. However, its main field of use is dentistry, where this type of laser is a cornerstone in oral surgery and implantology [3][4][5][6]. The Erbium laser emits at 2940 nm and is characterized by an active medium consisting of a Yttrium-Aluminium-Garnet (YAG) crystal doped with erbium ions [7,8].…”
Section: Introductionmentioning
confidence: 99%